White-collar crime: an opportunity perspective - Benson, Michael L. (Criminology and justice studies series, 2009)
What is white-collar crime -- Who is the white-collar offender -- Explaining white-collar crime : traditional criminological theories -- The nature of white-collar crime : opportunities and techniques -- Opportunity and white-collar property crimes -- Opportunity and corporate violence -- The symbolic construction of opportunity -- The social distribution of opportunity : class, gender, and race -- Control, prevention, and opportunity -- Opportunities and the future of white-collar crime